Application of The Triple Layered Business Model Canvas in Corporate Social Responsibility: Systematic Literature Review - Inggitana Widya Kumala Putri; Tiena Gustina Amran; Dadang Surjasa (OPSI, 2023)
The coronavirus (COVID-19) pandemic is still a main concern for various levels of society. Changes in people's lifestyles have triggered companies to switch to the right new business strategies to control their businesses during the COVID-19 pandemic. The unemployment rate, which increased by 7.07 percent due to the pandemic, needs to be suppressed by opening new jobs. The Triple Layered Business Model Canvas (TLBMC) is a method that can be used by Corporate Social Responsibility (CSR) to collaborate with the surrounding community in improving their quality of life during the pandemic. This research was conducted to identify the development of the TLBMC method, which can be obtained from literature studies from 2016 to 2022. The method used in this study is the Systematic Literature Review (SLR). This study uses the Exponential Comparison Method (MPE) to minimize bias in assessing the quality of the selected literature. The results showed that from 27 pieces of literature, nine top-selected literature with total scores above 5019 points could support research on applying TLBMC in CSR. This study found the importance of CSR collaboration with the community in restoring the economic cycle in the midst of the COVID-19 pandemic with the support of the TLBMC method.